2015
DOI: 10.1088/0004-637x/814/2/84
|View full text |Cite
|
Sign up to set email alerts
|

SPECTROSCOPIC STUDY OF STAR-FORMING GALAXIES IN FILAMENTS AND THE FIELD ATz∼ 0.5: EVIDENCE FOR ENVIRONMENTAL DEPENDENCE OF ELECTRON DENSITY

Abstract: We study the physical properties of a spectroscopic sample of 28 star-forming galaxies in a large filamentary structure in the COSMOS field at z∼0.53, with spectroscopic data taken with the Keck/DEIMOS spectrograph, and compare them with a control sample of 30 field galaxies. We spectroscopically confirm the presence of a large galaxy filament (∼8 Mpc), along which five confirmed X-ray groups exist. We show that within the uncertainties, the ionization parameter, equivalent width (EW), EW versus specific sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
90
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(116 citation statements)
references
References 224 publications
18
90
6
Order By: Relevance
“…The effects of the environment on the metal content of latetype galaxies has been debated for a long time (Shields et al 1991;Vílchez 1995;Skillman et al 1996;Pilyugin et al 2002;Mouhcine et al 2007;Ellison et al 2009;Hughes et al 2013;Peng & Maiolino 2014;Pustilnik et al 2013;Nicholls et al 2014;Darvish et al 2015;Kacprzak et al 2015;Kreckel et al 2015;Shimakawa et al 2015;Valentino et al 2015, among many others).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of the environment on the metal content of latetype galaxies has been debated for a long time (Shields et al 1991;Vílchez 1995;Skillman et al 1996;Pilyugin et al 2002;Mouhcine et al 2007;Ellison et al 2009;Hughes et al 2013;Peng & Maiolino 2014;Pustilnik et al 2013;Nicholls et al 2014;Darvish et al 2015;Kacprzak et al 2015;Kreckel et al 2015;Shimakawa et al 2015;Valentino et al 2015, among many others).…”
Section: Discussionmentioning
confidence: 99%
“…Darvish et al (2015) studied the properties of a sample of 28 starforming galaxies in a large filamentary structure at z ∼ 0.53 (using Keck spectroscopic data) and compared them with a control sample of 30 field galaxies. They found that, on average, star-forming galaxies in filaments are more metal-enriched (∼ 0.1 -0.15 dex).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the "galactic conformity"-the observation that satellites are more likely to be quenched around quiescent centrals than star-forming (SF) ones-has been found on both small and larger megaparsec scales (Weinmann et al 2006;Kauffmann et al 2013;Hartley et al 2015;Hearin et al 2015;Berti et al 2017;Hatfield & Jarvis 2016;Kawinwanichakij et al 2016), suggesting the role of the large-scale gravitational tidal field on galaxy properties. Moreover, several observations have found that the star formation activity and other galaxy properties depend on the large-scale cosmic web (Fadda et al 2008;Porter et al 2008;Biviano et al 2011;Darvish et al 2014;Ricciardelli et al 2014;Chen et al 2016b;Darvish et al 2015a;Guo et al 2015;Alpaslan et al 2016;Pandey & Sarkar 2016), whereas others have seen no or at best a weak dependence between the properties of galaxies and the global cosmic web environments (Alpaslan et al 2015;Eardley et al 2015;Filho et al 2015;Penny et al 2015;Alonso et al 2016;Beygu et al 2016;Brouwer et al 2016;Vulcani et al 2016a).…”
Section: For Reviews)mentioning
confidence: 99%
“…In pilot studies to target the cosmic web, Darvish et al (2014Darvish et al ( , 2015a used the 2D version of the MMF algorithm and applied it to potential large-scale structures in the COSMOS at z∼0.83 and 0.53. The z ∼ 0.83 structure clearly showed a filament linking several clusters and groups and was traced by the distribution of Hα emitters (Sobral et al 2011;Darvish et al 2014).…”
Section: For Reviews)mentioning
confidence: 99%
“…From a theoretical point of view, Aragon-Calvo et al (2016) showed that the star formation quenching in galaxies can be explained as the influence of filamentary environment, due to the non-linear interaction of the cosmic web. Meanwhile, a variety of case studies of particular filamentary structures have reported an increased fraction of star-forming galaxies (Fadda et al 2008;Tran et al 2009;Biviano et al 2011;Darvish et al 2014), and higher metallicities and lower electron densities (Darvish et al 2015) in filaments with respect to field environments. Unfortunately, most of these studies encompass a relatively small number of galaxies and limited volumes, making them sensitive to the cosmic variance.…”
Section: Introductionmentioning
confidence: 99%